The use of herbal medicines and related factors among diabetic patients - Rasyida, T. Syifa; Laoli, Elfani Dita Pradana; Ginting, Tariana; Sibagariang, Eva Ellya; Dameria, Dameria (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Diabetes mellitus (DM) is a chronic non-communicable disease characterized by elevated blood glucose levels due to insulin dysfunction. The use of herbal medicine has increased among patients with diabetes due to the widespread availability of information about herbal treatments globally. Many believe herbal remedies have minimal side effects and are more natural. The purpose of this study was to identify the factors associated with the use of herbal medicine among DM patients at Puskesmas Kampung Baru, Medan Maimun District. This quantitative, cross-sectional study was conducted from February to April 2025. The independent variables examined were age, education, income, knowledge, attitude, and belief, while the use of herbal medicine served as the dependent variable. The study population included all 809 registered DM patients at Puskesmas Kampung Baru. A sample of 189 was selected using a proportion difference test formula and a simple random sampling method. Bivariate data analysis was performed using the chi-square test. The results indicate that 164 (86.6%) respondents use herbal medicine. A significant association was found between herbal medicine use and age (p=0.019), income (p=0.000), knowledge (p=0.000), attitude (p=0.000), and belief (p=0.000). However, no significant association was found with education (p=0.089). Based on these findings, it is recommended that patients with diabetes mellitus receive counseling on the safe and evidence-based use of herbal medicine, with a strong emphasis on consulting healthcare professionals.